The Relationship between Responsible Leadership and individual work behaviors mediated by affective commitment - Simões, L. M.; Duarte, A.P. (​XVII PhD Meeting in Psychology, 2022)
In recent years, there have been scandals in the organizational world triggered by ethical lapses. These scandals discredit organizations, namely, in the way they operate in the market and the type of leaders they have, which has created tension in the relationship and trust of their stakeholders (Voegtlin et al., 2012; Waldman & Siegel, 2008). In response to this problem, a new type of leadership has been proposed: responsible leadership. This new leadership allows responding to the challenges that organizations are facing. The present study analyzes how responsible leadership explains individual work behaviors (individual performance and organizational citizenship behaviors) through the mediation of affective commitment. As a way of testing the proposed research model, a cross-sectional correlational quantitative methodology was used. The data was collected through an online questionnaire. 298 employees from different organizations operating in Portugal responded, voluntarily and anonymously, to the questionnaire. Data were analyzed using the PROCESS macro. The results indicated the existence of a significant relationship between employees' perceptions of responsible leadership and their individual work behaviors. Furthermore, affective commitment significantly mediates the relationship between responsible leadership and individual work behaviors, specifically individual performance, and organizational citizenship behaviors. This study reinforces the idea that organizations can increase their employees' affective commitment and, consequently, increase their individual performance and organizational citizenship behaviors by promoting the adoption of responsible leadership behaviors by their leaders.